Aging parents’ and middle-aged children’s evaluations of parents’ disability and life problems - Lee Hyo Jung (2020)
This study was supported by grants from the National Institute on Aging (NIA), R01AG027769, Family Exchanges Study II (Karen L. Fingerman, Principal investigator) and R03AG048879, Generational Family Patterns and Well-Being (Kyungmin Kim, Principal investigator). The MacArthur Network on an Aging Society (John W. Rowe, Network director) provided funds. This research also was supported by grant, 5 R24 HD042849 awarded to the Population Research Center (PRC) at The University of Texas at Austin by the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD).